Plant-based products: potential, production technology and challenges - Isabella Maciel Costa; Cosme Damião Barbosa; Nayana Hayss Araújo da Silva (The Journal of Engineering and Exact Sciences)
Consumers have become more interested in diets that provide health benefits and contain plant-based products. Therefore, the food industry has observed the demands and developed plant-based products. Vegetable extracts are water-soluble extracts based on vegetables, legumes, fruits, grains, cereals, pseudocereals, oilseeds or nuts that present different composition and sensory characteristics, depending on the raw material used. Meat substitutes, such as tofu and soy protein, have long been consumed by the population. However, nowadays there is a market demand for plant-based products that resemble animal products in taste, texture and appearance. One of the biggest challenges for the food industry is the development of new innovative products which do not contain ingredients of animal origin and contain nutritional support to act as a replacement for the daily consumption of the population. This work aimed to evaluate the possibility of elaborating plant-based products, the technologies used in the process, and the challenges involved. The study was characterized as a qualitative and bibliographic literature research. Scientific articles, monographs and reviews published between 2018 and 2022 were selected. Studies showed that technological innovations in the food industry produce plant extracts with better sensory characteristics and an increase in acceptability using additives and ingredients that provide a pleasant flavor and aroma. Thus, it was observed that plant-based products are promising and meet market demands, and new technologies have been used to improve their sensory characteristics. However, it is necessary to pay attention to the adequate supply of nutrients essential for the proper functioning of the body through a balanced diet recommended by nutrition professionals.